Exploring the Effects of Early Extramural English Exposure on the Vocabulary Size of University Students - Nicole Louise Busby (MDPI AG, 2024)
Research has shown that current informal extramural (out-of-class) activities can be an important predictor of second language (L2) vocabulary knowledge, but less is known about the relationship between language proficiency and activities earlier in life, which could have contributed to L2 acquisition. This exploratory study investigated Norwegian university students' reported exposure to English through extramural activities at an early age and how this related to their current vocabulary size in L2 English. Participants (N = 40) completed an online survey comprising items from the Vocabulary Size Test (VST) and questions about the earliest extramural activity they felt made an important contribution to their knowledge of L2 English and the age at which they engaged in this activity. Participants' mean English vocabulary size, as measured by the VST, was 11,246 words, and regression analysis found that the age of reported earliest extramural exposure was a significant predictor for L2 vocabulary size but that the current age of participants was not a significant predictor of VST scores. The results suggest that investigating early exposure to extramural input could be an important avenue for future research.